Effect of cooling strategy on physiological and perspective response of elite woman sailing athlete during exercise in warm environment: a case study - Nakamura, D.; Hasegawa, H.; Nakamura, M.; Hagiwara, M.; Takahashi, H. (Journal of High Performance Sport, 2019)
This case study aimed to investigate a method of effective body cooling between races in a female windsurfer in the Japanese National Team. The participant underwent race training in which they windsurfed two round trips on a course set by the coach. A resting period of approximately 20 minutes was set between the 1st and 2nd races and the cooling intervention was performed for 10 minutes under the following 3 conditions: (1) neck cooling with ice pack and forearm and hands water immersion up to the elbow in water (10°C). (NA condition); (2) neck and forearm cooling and ice slurry ingestion with 4 g.kg-1-BW (NAS condition) ; and (3) control condition without any intervention (CON condition). The results of this study showed that although the decline in core temperature was almost the same among the three conditions, the percent decline rate in HR and the decline of subjective thermal sensation was bigger in the NA and NAS conditions compared with the CON condition during the intervention period. Accordingly, these findings in this study may be used as a basic indication of effective counter measures during actual windsurfing competitions in female elite windsurfers in the heat.